Sectoral trends in earnings inequality and employment International trade, skill-biased technological change, or labour market institutions? - Stefan Thewissen; Chen Wang; Olaf van Vliet (Luxembourg Income Study (LIS), 2013)
Current studies addressing the rise in inequality confine themselves to country-level developments. This paper delineates trends in earnings inequality and employment at the sectoral level for eight LIS countries between 1985-2005. Earnings inequality mainly manifests itself within rather than between sectors. Yet, there is significant variation in the level of inequality across sectors whilst the differences between countries in intrasectoral inequality are much less pronounced. A general rise in intrasectoral earnings dispersion and a shift from the manufacturing industry towards the financial sector are perceptible. Crosssectional pooled time-series analyses indicate significant associations between the exposure to import and decreased employment within sectors, whilst no evidence is found for relations between earnings inequality and international trade or skill-biased technological change.
Keywords: D30; D63; E24; L60; 330; earnings inequality; sectoral approach; globalisation; skill-biased technological change; income inequality